Word Wall Website (W3): An Acceleration to boost the Vocabulary Mastery for Indonesian EFL Learners - Hikmawati Yusuf (Journal of Research Education and English Teaching, 2025)
The purpose of this study is to find out the significant effect of the use of the word wall website on enriching students' vocabulary mastery more effectively compared to traditional learning methods, such as reading, memorizing vocabulary, and to find out students' perceptions after using the word wall website in learning English vocabulary. The location of this research was at SMPN 4 Majene. This research used a quasi-experimental design. In this study, the population was class IX students, totaling 80 students; the samples of this study were two classes, consisting of 20 students each. The experimental group was taught using word wall website, while the control group used conventional methods. Treatment was conducted in 4 meetings. The research data was collected using two types of instruments, namely tests (pre-test and post-test) and student perception questionnaires. The results of data analysis showed that in the experimental group the mean post-test score (76.50) was higher than the mean pre-test score (70.50), it can be seen that the mean score of each class was increased, but the improvement in the experimental class is higher than the control class. In addition, Sig. (2-tailed) is 0.011 which is smaller than the significance level (0.05). This means that there is a significant difference between the mean value of students' post-test in the experimental group and the mean value of students' post-test in the control group. Therefore, the alternative hypothesis (H1) is accepted while the null hypothesis (H0) is rejected. The results of the student perception questionnaire related to the recapitulation of questionnaire data regarding the usefulness and enjoyment of the word wall website, show that most students have a very positive response to the use of the word wall website and produce an mean value (86%).